Condition of Women Prisoners in Model Jail, Chandigarh: A Communication Study - Dhiman, Bharat; Singh Malik, Pawan (International Journal of Psychosocial Rehabilitation, 2022)
A study on women prisoners is a special subject of research. A prison is an isolated social system and analyzed easier in terms of the social system than other cases, especially society as a whole is a too complex system to research it directly. This research study throws light upon the conditions of women prisoners in Model Jail, Chandigarh, and such conditions, which are currently burning problems. Women prisoners have to face several problems in prisons which can be described as cultural, communication, social, economic, physiological, environmental, psychological, etc. The researcher used primary and secondary source of data collection. The primary data by using a self-made structured interview schedule, observation method, and secondary data were collected by magazines, books, journals, newspapers, government records, and various published and unpublished works, etc.